The heterogenation of iron-carbonyl thiourea complex onto rice husk silica and its catalytic oxidation of limonene with hydrogen peroxide. - Nadiah Ameram (2017)
Three new thiourea ligands (2-methyl-N-[(2-pyridine-2-yl-ethy)carbamothioyl] benzamide, 02; 4-methyl-N-[(4-methylpyridin-2-yl)carbamothioy]benzamide, P1; and 4-methyl-N-[(2-pyridine-2-yl-ethyl)carbamothioyl]benzamide, P2) were synthesized and characterized by various spectroscopic and analytical techniques viz., NMR ('H and 1C), FTIR and elemental analysis. Molecular structure of three thiourea derivatives were established through single crystal X-ray diffraction technique. The ligands 02, P and P2 were immobilized using chloropropyltriethoxysilane (CPTES) as the anchoring agent onto rice husk ash (RHA). The resultant catalysts were designated as RHACO2, RHACPI and RHACP2. Spectroscopic characterisation confirmed the successful immobilization of the organic ligands on the silica framework. The 2Si MAS NMR of RHACP1 and RHACP2 showed the presence of T', T, Q and Qwhile the T?, T, Qand Q were present in RHACO2. The C MAS NMR showed the chemical shifts of -CH:CHCH;-moiety. RHACO2 had chemical shifts at 24.97, 41.72 and 62.82 ppm while RHACP1 and RHACP2 had chemical shifts at 23.52, 40.17, 60.40 ppm, 26.68, 47.86 and 63.02 ppm respectively. The C MAS NMR demonstrated that all the catalysts have a series of chemical shifts which is compatible with the existence of pyridine ring and aromatic benzene ring. In this study, these catalysts have been used in the oxidation of limonene. The main product obtained was limonene epoxide (LO) with many side products. Limonene epoxide which is the principle compound would be vital as intermediates for organic synthesis for various uses such as in pharmaceutical products, food additives, and scents. Based on the optimum parameters, the order of the catalyst's reactivity was found to be: RHACP1> RHACO2> RHACP2. The higher steric effect of P2 seems to be the reasons for the low reactivity of RHACP2 compared to RHACP1. The yield of LO obtained for RHACO2, RHACP1 and RHACP2 were 40.02 %, 63.20 % and 25.65 % respectively. PI ligand was complexed with iron (1I). The potential to utilize iron in this chemical processes is due to its low cost and eco-friendlyness. The resulting metal complex was immobilized onto RHA silica to produce a new catalyst, RHACPIFe. It was characterized and used in the oxidation of limonene. The main product was limonene epoxide while the side products were limited only to carvone and carveol. It was found that the incorporation of the iron(11) resulted in the drastic reduction of the number of side products (carvone and carveol). The yield of LO was found to be 46.23 % with 69.00 % of limonene conversion and 67.00 % of LO selectivity. Filtration can be used to efficiently recover these catalysts. These catalysts are reused for a minimum of three times without considerable loss in its catalytic action.